STORYTELLING BONEKA DALAM MENINGKATKAN PERSONAL SAFETY SKILLS ANAK USIA DINI SEBAGAI PENCEGAHAN KEKERASAN SEKSUAL - Salsabila, Galuh Nurfairuz; Scarvanovi, Berliana Widi (JIP (Jurnal Intervensi Psikologi), 2024)
Sexual violence in Indonesia is increasingly prevalent across all ages and genders. Children are particularly vulnerable due to their lack of sexual education, underscoring the need to impart personal safety skills early. This study investigates the impact of puppet storytelling on enhancing young children's personal safety skills as a preventive measure against sexual violence. The subjects, aged 4-6 years and without prior sexual education, were divided into experimental and control groups of 25 children each. This quasi-experimental study utilized a non-equivalent control group design and was analyzed using the non-parametric Mann Whitney test, which showed a significant difference (Sig. 0.000 < 0.005) in the post-test and pre-test scores between the groups after the intervention. The findings indicate that puppet storytelling significantly improves the personal safety skills of young children, demonstrating the method's relative effectiveness when introduced at an early age.